Fisher-Modigliani-Miller organisational finance theory and the financialisation of contemporary societies. Issue 4 (4th July 2021) - Cardao-Pito, Tiago
Abstract: Apart from followers as Milton Friedman, Paul Samuelson, Ronald Coase, and Maurice Allais, most economists abandoned Irving Fisher's economic framework after the post-1929 Great Crisis. Without citing Fisher however, in 1958 Franco Modigliani and Merton Miller reutilised his framework to found the organisational finance theory awarded several Nobel prizes. This organisational finance theory is highly supportive of the financialisation of societies. It advocates that organisations exist to maximise their owners'/shareholders' wealth, a 'perfect markets fallacy', and the elimination of taxes and regulations. Furthermore, it contends an unverified separation theorem between financial and productive sectors, or among financial, investing, and operating decisions.